1995
DOI: 10.1002/pd.1970150704
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of trisomy 9. Six cases and a review of the literature

Abstract: Six prenatally diagnosed cases of trisomy 9 are reported and 22 previously reported cases are reviewed; the difficulty of genetic counselling for such cases and the variation in the percentage of trisomic cells in different tissues, thus making accurate diagnosis of trisomy 9 difficult, are emphasized. In addition to karyotyping results, ultrasound findings are important in achieving diagnoses. Finally, a course of action when prenatal trisomy 9 is detected is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…Much of the available literature on trisomy 9 focuses on reports concerning results of prenatal testing including sonographic findings [e.g., Francke et al, 1975;Schwartz et al, 1989;Benacerraf et al, 1992;Saura et al, 1995] or fetal autopsy [Chitayat et al, 1995]. Schwartz et al [1989] describe the physical characteristics in a fetus with trisomy 9 mosaicism including micrognathia, skeletal malformations and cardiac malformations.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the available literature on trisomy 9 focuses on reports concerning results of prenatal testing including sonographic findings [e.g., Francke et al, 1975;Schwartz et al, 1989;Benacerraf et al, 1992;Saura et al, 1995] or fetal autopsy [Chitayat et al, 1995]. Schwartz et al [1989] describe the physical characteristics in a fetus with trisomy 9 mosaicism including micrognathia, skeletal malformations and cardiac malformations.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, extreme discordance between tissue cultures have been noticed in trisomy 9 pregnancies by several authors. Saura et al [14] reported a case in which chorionic villus sampling and amniocentesis revealed a nonmosaic trisomy 9 but postmortem tissue samples demonstrated no abnormal cell lines in the placenta, amnion, or skin, although a 60% mosaicism in the colon and 100% trisomy 9 cells in the lungs were found. Sherer et al [16] reported a similar case, in which nonmosaic trisomy 9 was identified by amniocentesis at 31 weeks of gestation but no trisomy 9 cell lines were found in either the neonatal umbilical cord or neonatal peripheral blood, although skin fibroblasts showed trisomy 9 in 10% of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal diagnosis of nonmosaic trisomy 9 has scarcely been reported in the literature [12][13][14][15], most cases being diagnosed by chorionic villous sampling or amniocentesis performed for routine indications, mainly advanced maternal age. In a recent review of the literature, Saura et al [14] reported 6 cases of trisomy 9 and compiled a total of 28 cases from the literature. Among the 23 cases in which karyotype from amniotic fluid culture was available, which implies that the pregnancy had progressed beyond the first trimester, 5 were diagnosed as having a nonmosaic trisomy 9 but only 2 confirmed as such by karyotype culture from at least one other tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In mosaic cases, which are clinically milder than nonmosaic ones, various numbers of abnormal cells may be detected in different tissues including the amniotic fl uid, the placenta, lymphocytes, skin fi broblasts, the lung, the kidney, and the ovary [5] . + = Finding present; U/S = sonographic fi ndings; NB = external and radiographic fi ndings of the stillborn infant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, results of chorionic villus sampling or umbilical cord blood sampling should be interpreted with great caution. However, it should be noted that amniotic fl uid is considered the best single specimen for karyotyping for trisomy 9 [5] , because cells in the amniotic fl uid originate in various fetal tissues. In the present case, we made a diagnosis of nonmosaic disease based on the results from 20 amniotic cells.…”
Section: Discussionmentioning
confidence: 99%